2008 7th IEEE/ACM International Symposium on Mixed and Augmented Reality 2008
DOI: 10.1109/ismar.2008.4637341
|View full text |Cite
|
Sign up to set email alerts
|

Label segregation by remapping stereoscopic depth in far-field augmented reality

Abstract: This paper describes a novel technique for segregating overlapping labels in stereoscopic see-through displays. The present study investigates the labeling of far-field objects, with distances ranging 100-120 m. At these distances the stereoscopic disparity difference between objects is below 1 arcmin, so labels rendered at the same distance as their corresponding objects appear as if on a flat layer in the display. This flattening is due to limitations of both display and human visual resolution. By remapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Dynamic scenes (including moving labels) yielded lower error rates than static scenes. An earlier experiment [30] found that correct vertical separation based on depth yielded lower error than no vertical separation and inverted vertical separation. Correct vertical separation meant that the closest target, which was lowest in the visual field, had the lowest label in the visual field.…”
Section: Text Legibilitymentioning
confidence: 92%
“…Dynamic scenes (including moving labels) yielded lower error rates than static scenes. An earlier experiment [30] found that correct vertical separation based on depth yielded lower error than no vertical separation and inverted vertical separation. Correct vertical separation meant that the closest target, which was lowest in the visual field, had the lowest label in the visual field.…”
Section: Text Legibilitymentioning
confidence: 92%
“…They found that users were able to read labels fastest for algorithms that focused on preventing overlap, the key attribute for response time. Peterson et al [15] looked at label segregation in stereo vision at far distances (100-120 m) using an optical see-through display. They presented a method for segregation that reduces the cost imposed by traditional label placement methods.…”
Section: General Positioning Depth and Sizing Cuesmentioning
confidence: 99%
“…Since previous HMDs outdoor evaluation studies have shown that text and colours could appear altered or washed out on the displays in daylight; an additional setting to adjust the AR app for outdoor use was considered. Previous studies [32], [33] recommend augmented elements to be 10-15% brighter than the background; this is in order to make them visible on a stereoscopic display. Hence, the daylight intensity level is used to adjust the brightness of virtual elements and 3D objects.…”
Section: The Proposed T1/t2 Fuzzy Logic Based Gis-ar Systemmentioning
confidence: 99%